Uncovering Beta-Lactam Susceptibility Patterns in Clinical Isolates of Mycobacterium tuberculosis through Whole-Genome Sequencing - Olivença, Francisco (2022)
The increasing threat of drug resistance and a stagnated pipeline of novel therapeutics endanger the eradication of tuberculosis. Beta-lactams constitute promising additions to the current therapeutic arsenal and two carbapenems are included in group C of medicines recommended by the WHO for use in longer multidrug-resistant tuberculosis regimens. However, the determinants underlining diverse Mycobacterium tuberculosis phenotypes to beta-lactams remain largely undefined. To decipher these, we present a proof-of-concept study based on a large-scale beta-lactam susceptibility screening for 172 M. tuberculosis clinical isolates from Portugal, including 72 antimycobacterial drug-resistant strains. MICs were determined for multiple beta-lactams and strains were subjected to whole-genome sequencing to identify core-genome single-nucleotide variant-based profiles. Global and cell wall-targeted approaches were then followed to detect putative drivers of beta-lactam response. We found that drug-resistant strains were more susceptible to beta-lactams, but significant differences were not observed between distinct drug-resistance profiles. Sublineage 4.3.4.2 strains were significantly more susceptible to beta-lactams, while the contrary was observed for Beijing and 4.1.2.1 sublineages. While mutations in beta-lactamase or cell wall biosynthesis genes were uncommon, a rise in beta-lactam MICs was detected in parallel with the accumulation of mutations in peptidoglycan cross-linking or cell division genes. Finally, we exposed that putative beta-lactam resistance markers occurred in genes for which relevant roles in cell wall processes have been ascribed, such as rpfC or pknA. Genetic studies to validate the relevance of the identified mutations for beta-lactam susceptibility and further improvement of the phenotype-genotype associations are needed in the future. IMPORTANCE Associations between differential M. tuberculosis beta-lactam phenotypes and preexisting antimycobacterial drug resistance, strain sublineage, or specific mutational patterns were established. Importantly, we reveal that highly drug-resistant isolates of sublineage 4.3.4.2 have an increased susceptibility to beta-lactams compared with other strains. Thus, directing beta-lactams to treat infections by specific M. tuberculosis strains and refraining its use from others emerges as a potentially important strategy to avoid resistance development. Individual mutations in blaC or genes encoding canonical beta-lactam targets, such as peptidoglycan transpeptidases, are infrequent and do not greatly impact the MICs of potent carbapenem plus clavulanic acid combinations. An improved understanding of the global effect of cumulative mutations in relevant gene sets for peptidoglycan and cell division processes on beta-lactam susceptibility is also provided.